2015
DOI: 10.1155/2015/747036
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cytokines and Adhesion Molecules in the First 72 Hours after Severe Trauma: Association with Severity and Outcome

Abstract: Introduction. Severity and outcome assessments are crucial in trauma. Our aim was to describe the role of a group of cytokines (TNFα, IL-6, IL-10, and HMGB-1) and ICAM-1 as severity and outcome assessment tools and their kinetics in the first 72 h after severe trauma. Materials and Methods. Authors designed a prospective cohort study of severe polytrauma patients (ISS > 15) in a level 1 Trauma Centre. Cytokines and ICAM-1 levels and Th1/Th2 ratios were assessed at admission, 24, 48, and 72 h. SIRS, SIRS with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 24 publications
2
42
0
1
Order By: Relevance
“…First, injury severity may explain the results. Proinflammatory cytokine concentrations relate to the degree of tissue injury [44,100]. Although the injury may have been insufficient to stimulate specific cytokines detectably, the cumulative effect of cytokines may underlie detectable CRP production.…”
Section: Elevation Of Crp But Not Primary Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…First, injury severity may explain the results. Proinflammatory cytokine concentrations relate to the degree of tissue injury [44,100]. Although the injury may have been insufficient to stimulate specific cytokines detectably, the cumulative effect of cytokines may underlie detectable CRP production.…”
Section: Elevation Of Crp But Not Primary Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…IL-6: (1) ARDS; two studies [37,45] could not relate ARDS to IL-6 concentration alterations, whereas two other studies [48,51] found a positive correlation (Table 2); (2) Sepsis; five studies [35,41,46,47,53] found an increased IL-6 production to be predictive for the development of sepsis, whereas five other studies [28,29,38,39,55] did not (Table 3); (3) MODS; all five prospective cohort studies [3,28,34,46,51] concluded that IL-6 is markedly increased in the early development of MODS ( Dekker ABE et al . Do cytokines predict polytrauma outcome IL-10: (1) Three studies, two prospective [54,57] and one retrospective [14] , could not relate the serum IL-10 concentrations to the development of ARDS.…”
Section: Value Of Main Cytokine Concentrations For Predicting Complicmentioning
confidence: 97%
“…Do cytokines predict polytrauma outcome IL-10: (1) Three studies, two prospective [54,57] and one retrospective [14] , could not relate the serum IL-10 concentrations to the development of ARDS. One study [51] found IL-10 to be significantly higher in patients with ARDS; (2) Of the five reviewed studies, three prospective [29,50,54] and one retrospective study [14] found the IL-10 concentration to be predictive for the development of sepsis, whereas one prospective study [53] did not; (3) Two studies [51,54] reported IL-10 to be significantly elevated in patients with MODS, and two studies [3,57] could not find an association between the cytokine and development of MODS; and (4) According to five studies [13,32,33,36,50] the serum IL-10 concentration was significantly higher in MOF patients. One study showed no significant elevation [27] .…”
Section: Value Of Main Cytokine Concentrations For Predicting Complicmentioning
confidence: 99%
See 2 more Smart Citations